Tool Development Effectiveness Display Mirrors and Lenses (Multi shapes) as a Physics Learning Media with ADDIE Design - Dewi Arisanti; Derlina Derlina; Rahmatsyah Rahmatsyah (Universitas Lambung Mangkurat, 2022)
They were teaching aids as the indispensable components in visualizing the learning concepts to be studied, especially in learning the Physics of optical material. This makes it easier for students to describe each concept learned in their language during the visualization process. The purpose of this research is the effectiveness of multi shapes aquarium props as a learning media developed by design Analyze, Design, Development, Implementation, Evaluation (ADDIE). This study uses the Research and Development (R&D) method to assess the effectiveness of the development of teaching aids with the ADDIE design. The results showed that the effectiveness of mirror and lens teaching aids (multi shapes) based on the evaluation of classical learning using mirrors and lenses (multi shapes) props by 90% of students completed with observations of student activities of 79.67%.